Surgically treatment of proximal humerus fractures - V A Markin; S V Sergeev; A Isaak (RUDN Journal of Medicine, 2008)
Analysis of results of 43 surgically treated patients with fractures of the proximal humerus (26 males and 17 females) was carried out Average age of patients was 42,4 yrs. A differential approach in treatment of the patients was depended on the character of fracture, bone stock and age. Traditional T-plates, LCP, locking nails and prosthetics were implanted. Indications were defined for the particular method of osteosynthesis. Rehabilitation in operated patients began on the 2 and 3 post-operative days. 81,4% cases showed excellent and good results.